A variable fixed‐focus constant optimization method for a variable‐included‐angle varied‐line‐spacing plane‐grating monochromator. (11th June 2019) - Xue, Chaofan; Xue, Lian; Wu, Yanqing; Wang, Yong; Yang, Shumin; Tai, Renzhong
Abstract : A variable C ff optimization method is introduced for a variable‐included‐angle varied‐line‐spacing plane‐grating monochromator. By adopting this method, the C ff value can be arbitrarily selected in the monochromator. Abstract : Variable‐included‐angle varied‐line‐spacing plane‐grating monochromators (VIA‐VPGM) have been applied to many beamlines because of the self‐focusing and aberration‐correction function of the varied‐line‐spacing grating. Unfortunately, to optimize the variable‐line‐spacing coefficient of the grating, the fixed‐focus constant ( C ff ) has to be fixed first in the VIA‐VPGM. In this way, some of the advantages of these monochromators are lost, such as the flexibility of choosing a different energy‐resolving power by varying the C ff . In this work, a variable C ff optimization method is introduced for a VIA‐VPGM. By adopting this method, the C ff could be arbitrarily selected in the VIA‐VPGM.